Measurement of the top quark pair production cross section in p p̄ collisions - Abachi, S; Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alves, G; Amidi, E; Amos, N; et al. (1997)
We present a measurement of the tt̄ production cross section in pp̄ collisions at √s = 1.8 TeV by the D0 experiment at the Fermilab Tevatron. The measurement is based on data from an integrated luminosity of approximately 125 pb-1 accumulated during the 1992-1996 collider run. We observe 39 tt̄ candidate events in the dilepton and lepton + jets decay channels with an expected background of 13.7 ± 2.2 events. For a top quark mass of 173.3 GeV/c2, we measure the tt̄ production cross section to be 5.5 ± 1.8 pb.